Synthesis and characterisation of novel 1,2,4-triazole containing manganese-based metal-organic frameworks as emerging electrodes for supercapattery device - Raman, Velan (2023)
(SCs) are essential in addressing the need for sustainable energy issues caused by the depletion of fossil fuels. Despite extensive study and substantial progress of both SCs and batteries have been carried out, individual device performance still requires further development to fulfil current commercial expectations. Batteries have high specific energy despite having low specific power. On the other hand, SCs with low specific energy prevent them from being widely used in commercial applications. Thus, this scenario sparked a new line of inquiry, by integrating the battery and SCs into a single device known as a supercapattery. This device is predicted to have outstanding performance and a long cycle life due to the combination of capacitive and battery-grade materials. However, supercapattery technology is still developing since the current focus is on the development of high-performance novel electrode materials to design supercapattery devices. Metalorganic frameworks (MOFs) have attracted a lot of attention in the field of energy storage due to their unique properties, including large specific surface areas, adjustable pore sizes and stable porous structures. Therefore, the synthesis of novel MOFs and fabrication of them as electrode materials in supercapattery devices are essential goals in current research. Three novel Mn(II) MOFs bonded to 1,2,4-triazoles (Htrz) ligand namely UPMOF-4 (MnCl2.4H2O with Htrz), UPMOF-5 (anhydrous MnBr2 with Htrz) and UPMOF-6 (Mn(NO3)2.4H2O with Htrz) were successfully synthesised solvothermally with molar ratios of 1:2 (UPMOF-4 and UPMOF-5), 1:1.5 (UPMOF-6) at 125°C (UPMOF-4), 120°C (UPMOF-5) and 110°C (UPMOF-6). These new MOFs were characterised using powder Xray diffraction (PXRD), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), N2 physisorption analysis and the structural determination was performed by single-crystal X-ray diffraction analysis (SCXRD). The peaks at low angles of 10° in the PXRD pattern of MOFs indicated the formation of a large unit cell of the frameworks. Thermal analysis revealed that UPMOF-4, UPMOF-5 and UPMOF-6 had high thermal stability up to 490°C, 570°C and 435°C, respectively. The N2 adsorption-desorption measurements indicated the UPMOF-4, UPMOF-5 and UPMOF-6 had BET surface areas of 1758 m2/g, 1724 m2/g and 895 m2/g, respectively. The three novel MOFs were crystallised in a monoclinic system with different space groups, i.e. I2/a (UPMOF-4) and P21 (UPMOF- 5 and UPMOF-6). Topologically, the three-dimensional (3D) structure of UPMOF-4 owns a pcu network topology while UPMOF-5 and UPMOF-6 with two-dimensional (2D) structures displayed hxl type topology. The novel MOFs were then utilised as positive electrodes for electrochemical studies as supercapattery devices for the first time. In a threeelectrode assembly in 1 M KOH, all three MOFs manifested a decent performance by showing a battery-graded nature with specific capacities of 203.1 C/g (UPMOF-4), 160.2 C/g (UPMOF-5) and 121.1 C/g (UPMOF-6). The novel MOFs were sandwiched with activated carbon (negative electrode) to fabricate supercapattery devices. UPMOF-4 showed a good specific capacity of 174.4 C/g with promising capacity retention of 90.1% even after 2500 cycles, whereas UPMOF-5 and UPMOF-6 depicted specific capacities of 132.4 C/g and 96.28 C/g with capacity retention of 88.9% and 79.9%, respectively after 2500 cycles. The density functional theory (DFT) calculation of these three MOFs revealed that UPMOF- 4 has the lowest HOMO-LUMO energy gap (Egap) of 0.211 eV followed by UPMOF-6 (0.777 eV) and UPMOF-5 (1.198 eV). Therefore, the good electrochemical performance of UPMOF-4 imputed to the structural stability, highly porous nature and low Egap. This work indicated that all these MOFs could be emerging electrode materials for supercapattery devices.